2018
DOI: 10.3389/fmicb.2018.00348
|View full text |Cite
|
Sign up to set email alerts
|

RovM and CsrA Negatively Regulate Urease Expression in Yersinia pseudotuberculosis

Abstract: Urease acts as an important acid resistance system and virulence factor that is widespread among microorganisms. RovM is a global regulator that regulates a series of genes and pathways including acid survival systems in the enteric bacterium Yersinia pseudotuberculosis (Yptb). However, whether RovM regulates the urease activity in Yptb was still unknown. In this study, by using qualitative and quantitative urease assays, we show that the urease expression responds to nutrient conditions and the RovM protein r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…The csrB ::Tn5 mutant also produced much less urease, and no urease activity was detected using Y. pestis KIM6+. During the preparation of this manuscript, it was also reported by Dai et al that CsrA represses urease production in Yptb strain YPIII, which is consistent with our results (Dai et al, 2018 ).…”
Section: Resultssupporting
confidence: 93%
“…The csrB ::Tn5 mutant also produced much less urease, and no urease activity was detected using Y. pestis KIM6+. During the preparation of this manuscript, it was also reported by Dai et al that CsrA represses urease production in Yptb strain YPIII, which is consistent with our results (Dai et al, 2018 ).…”
Section: Resultssupporting
confidence: 93%
“…Secondly, Gao et al ’s comparative transcriptomic analysis found that that rovM expression was not affected in an ompR ‐negative mutant (Gao et al , ). Thirdly, the urease locus in Yersinia pseudotuberculosis (the recent ancestor of Y. pestis ) is regulated by OmpR and the carbon storage regulator (Csr)‐RovM cascade because both OmpR and RovM bind to the urease locus promoter and not because OmpR regulates rovM (Achtman et al , ; Hu et al , ; Dai et al , ). Even though it has been suggested that RovM is involved in Y. pestis ’s metabolic adaptation to the flea gut (because it provides a fitness advantage), it has been clearly stated that RovM does not contribute to biofilm blockage or Y. pestis ’s growth or survival in the flea gut (Vadyvaloo et al , ).We therefore hypothesize that during flea infection, nutrient cues activate the Csr‐RovM regulatory cascade and the OmpR‐EnvZ regulatory system independently.…”
Section: Discussionmentioning
confidence: 99%
“…The chromosomal deletion mutants were constructed by sacB -based allelic exchange [ 24 ]. Two DNA fragments were amplified by PCR with C. sakazakii BAA-894 chromosomal DNA as a template with primer pairs UP-F/UP-R and DOWN-F/DOWN-R, respectively ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%